Strategi dalam Tindakan Pencegahan COVID19 Melalui Surveilans dan Promosi Kesehatan - Nisa, Alfiana Ainun; Rahayu, Tandiyo; Azam, Mahalul; Wijayanti, Yuni; Budiono, Irwan; Fauzi, Lukman (HIGEIA (Journal of Public Health Research and Development), 2021)
Indonesia is in danger because of the low awareness of the community to carry out social and physical distancing so that it can cause the spread of the virus to become increasingly difficult to control. Escalation of COVID-19 cases as of May 12 2020 in Central Java was 66 deaths, 980 confirmed and 229 recovered. One of the recommendations of the Ministry of Health in dealing with the COVID-19 epidemic is to carry out surveillance and response to COVID-19 extraordinary events. Universitas Negeri Semarang (UNNES) implemented the recommendation by conducted periodic surveillance which was used to detect COVID-19 earlier during outbreak period. Students and employees filled out the COVID-19 vigilance surveillance form online. Then data analysis, contact tracing / follow-up, and dissemination of COVID-19 vigilance surveillance results were carried out. A total of 8360 respondents in two period have filled out the vigilance surveillance form. A total of 75.41% had no symptoms, 10.28% had a cough, and 1.21% had a history of fever > 38Ã‚Â°C. Based on surveys of comorbidities as many as 1.32% have a history of hypertension and as much as 1.32% have asthma. Based on risk factors as much as 7.78% had visited health facilities as patients or visitors, as many as 1.38% of respondents had a history of close contact with People Under Monitoring (in first period). As many as 0.90% had visited other countries and 38.44% had visited other cities / regencies. We conclude that the majority of respondents have no symptoms, do not have concomitant conditions and have no risk factors for exposure to COVID-19. This survey can be used to measure prevention and early detection of COVID-19. It is necessary to deepen epidemiological and clinical characteristics as a more comprehensive step for screening respondents. Keywords: COVID19, Surveillance, Preventive Measures